Participatory plant breeding: Proceedings of a workshop on participatory plant breeding, 26-29 July 1995, Wageningen, The Netherlands - Eyzaguirre, Pablo B.; Iwanaga, M. (1996)
The papers in this volume were originally presented at a workshop on participatory plant breeding. The workshop was convened to crystallize a novel approach that plant breeders, genetic resource conservationists and social scientists were demonstrating with increasing success. That approach is to place knowledge about genetic resources, as well as enhanced germplasm, directly at the disposal of farmers for them to use and develop according to their own needs and practices. Experiences indicated that in using this approach, biological and social scientists were learning a great deal about the useful diversity in target crops and farming system. Farmers were also benefiting from access to greater diversity and from the partnerships they were forming with plant breeders.